2014
DOI: 10.3389/fphar.2014.00208
|View full text |Cite
|
Sign up to set email alerts
|

Application of insulin-like growth factor-1 in the treatment of inner ear disorders

Abstract: Sensorineural hearing loss (SNHL) is considered an intractable disease, given that hair and supporting cells (HCs and SCs) of the postnatal mammalian cochlea are unable to regenerate. However, with progress in regenerative medicine in the 21st century, several innovative approaches for achieving regeneration of inner ear HCs and SCs have become available. These methods include stem cell transplantation, overexpression of specific genes, and treatment with growth factors. Insulin-like growth factor-1 (IGF-1) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 83 publications
0
29
0
Order By: Relevance
“…Genetic studies of hundreds of genes necessary for audition have uncovered several pathways important for normal hearing. Based initially upon studies of animal model, growth factors are now being explored for treatment of noise and ototoxic induced deafness and age-related hearing loss, [100][101][102][103][104][105][106][107][108][109] and some of these are currently in clinical trials. 110,111 For example, topical application of IGF1 to the middle ear was used to treat sudden sensorineural hearing loss in humans, and some treated individuals showed improvements of 10 to 30 dB for tested frequencies as compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic studies of hundreds of genes necessary for audition have uncovered several pathways important for normal hearing. Based initially upon studies of animal model, growth factors are now being explored for treatment of noise and ototoxic induced deafness and age-related hearing loss, [100][101][102][103][104][105][106][107][108][109] and some of these are currently in clinical trials. 110,111 For example, topical application of IGF1 to the middle ear was used to treat sudden sensorineural hearing loss in humans, and some treated individuals showed improvements of 10 to 30 dB for tested frequencies as compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…110,111 For example, topical application of IGF1 to the middle ear was used to treat sudden sensorineural hearing loss in humans, and some treated individuals showed improvements of 10 to 30 dB for tested frequencies as compared to controls. 103,112 Hair cell regeneration in response to application of growth factors and by inhibition of specific signaling pathways is also being explored. 113 For example, an inhibitor of NOTCH signaling is in phase II clinical trial for treatment of sensorineural moderate to severe hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular occlusion is a potential cause of impaired cochlear perfusion, and risk factors, including factor V Leiden and prothrombin G20210A that lead to vascular perfusion defects, are also suspected to be important in SSHL (22)(23)(24). By contrast, inner ear damage was also associated with SSHL and Yamamoto et al reported that insulin-like growth factor-1, a growth factor involved in the development of the human inner ear, enhanced the regeneration of hair cells damaged in SSHL (25). Genetic factors associated with SSHL have generated significant interest.…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by clinical trial of IGF-1 treatment on human SSHL as well as in vivo animal experiments, which has confirmed its efficacy in hair cell injuries. 15 In a recent study, fractionated diet with glucose restriction was effective for the treatment of vestibular dysfunction associated with glucose metabolism disorders. 16 Disorders of glucose metabolism are considered the most common aetiology of metabolic labyrinthine disorders as per previous studies.…”
mentioning
confidence: 99%